2017
DOI: 10.18632/oncotarget.19243
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the T790M resistance mutation during afatinib treatment in EGFR tyrosine kinase inhibitor-naïve patients with non–small cell lung cancer harboring EGFR mutations

Abstract: The T790M secondary mutation of the epidermal growth factor receptor (EGFR) gene accounts for 50% to 60% of cases of resistance to the first-generation EGFR tyrosine kinase inhibitors (TKIs) gefitinib and erlotinib. The prevalence of T790M in EGFR mutation–positive patients who acquire resistance to the irreversible, second-generation EGFR-TKI afatinib has remained unclear, however. We here determined the frequency of T790M acquisition at diagnosis of progressive disease in patients with EGFR-mutated non–small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 17 publications
10
52
2
Order By: Relevance
“…Our comprehensive assessment based on the T/A ratio indicated that T790M was positive in 13 (52.0%) of 25 patients at the time of systemic PD development (Table , Figure ). Median PFS for treatment with afatinib was longer in patients with than in those without T790M at systemic PD (15.1 vs 10.9 months, P = 0.25; Figure B), consistent with previous findings . Although median time to systemic PD was longer than median PFS in patients with T790M at systemic PD (17.9 vs 15.1 months), such a difference was not apparent in patients without T790M at this time (10.9 vs 10.9 months; Figure C).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our comprehensive assessment based on the T/A ratio indicated that T790M was positive in 13 (52.0%) of 25 patients at the time of systemic PD development (Table , Figure ). Median PFS for treatment with afatinib was longer in patients with than in those without T790M at systemic PD (15.1 vs 10.9 months, P = 0.25; Figure B), consistent with previous findings . Although median time to systemic PD was longer than median PFS in patients with T790M at systemic PD (17.9 vs 15.1 months), such a difference was not apparent in patients without T790M at this time (10.9 vs 10.9 months; Figure C).…”
Section: Discussionsupporting
confidence: 89%
“…Among the 14 plasma samples in which EGFR activating mutations were detected at the time of systemic PD development by NGS, the detection rate for T790M by NGS was 71.4% (10 of 14; ). These detection rates for T790M are much higher than those previously reported for tumor samples collected from patients who experienced resistance to first‐ or second‐generation EGFR‐TKI . Although such a high frequency of T790M might be the result of selection bias due to the small number of samples, we considered the possibility that highly sensitive methods such as dPCR and NGS might detect a small population of T790M alleles in cfDNA that is not responsible for resistance to EGFR‐TKI and give rise to the low specificity of plasma analysis for the detection of T790M compared with tumor analysis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Unfortunately, the five‐year survival rate of NSCLC still remains unsatisfactory because of early tumor metastasis and relapse in spite of great development of treatment method (Miller et al, ). In addition, it is of great significance to investigate mutant abundance in NSCLC due to the clinical response and prolongation of survival (Obradović et al, ; Tanaka, Nosaki, Otsubo, Azuma, & Sakata, ). Therefore, it is urgent to find novel therapeutic strategies to limit NSCLC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Emergence of T790M gatekeeper mutation is the most frequent mechanism of acquired drug resistance to first- and second-generation EGFR-tyrosine kinase inhibitors (TKIs) [4, 5]. Osimertinib, a third-generation EGFR-TKI, is a specific drug to overcome T790M resistance mutation.…”
Section: Introductionmentioning
confidence: 99%